Answer:
we know that in one minute the toddler is 2(270)=540 feet and mother is 580 so less than 1 minute

How much compound interest is earned on $4300 at 2.9% interest for 10 years, compounded quarterly?

Evaluate. f(x) = 2x - 1, f(2)

What's the circumference of a circle with a diameter of 12 ft

Solve: 4y - 6 = 2y + 8

Can u pls explain to me how to do this?

Evaluate. f(x) = 2x - 1, f(2)

What's the circumference of a circle with a diameter of 12 ft

Solve: 4y - 6 = 2y + 8

Can u pls explain to me how to do this?

So: the baking pan is a cylinder so you need the equation which gives you the volume of a cylinder. This is the area of the base of the cylinder multiplied by the height of the cylinder.

The base is a circle and you know the radius. The area of a circle is radius^2*pi.

Therefore: 6^2 * 3.14 = 113.04

Now, you know the volume of the batter which is poured into the pan: 550 cm^3. You know the area of the base of the cylinder: 113.04. You only need the height, which you can calculate.

550 = 113.04 * height

Divide by 113.04

4.9 = height.

The base is a circle and you know the radius. The area of a circle is radius^2*pi.

Therefore: 6^2 * 3.14 = 113.04

Now, you know the volume of the batter which is poured into the pan: 550 cm^3. You know the area of the base of the cylinder: 113.04. You only need the height, which you can calculate.

550 = 113.04 * height

Divide by 113.04

4.9 = height.

**Answer:**

**The product of **

**Step-by-step explanation:**

Given : Two expressions (x + 3) and (2x – 1)

We have to find the product of given expression that is

Consider the given expression

Multiply each term of first bracket with each term of second bracket

we have,

Simplify,

we have

Simplify, we get,

Adding like terms, we have,

**Thus, the product of **

Umm

(X+3)(2x-1)

=2x square -x + 6x - 3

=2x square +5x -3

(X+3)(2x-1)

=2x square -x + 6x - 3

=2x square +5x -3

x -5 > -2 x > 5-2 x>3 {x | x R, x>3}

2x + 1y = 3 ⇒ 8x + 4y = 12

-4x - 4y = -8 ⇒ -4x - 4y = -8

4x = 4

4 4

x = 1

2x + y = 3

2(1) + y = 3

2 + y = 3

- 2 - 2

y = 1

(x, y) = (1, 1)

-4x - 4y = -8 ⇒ -4x - 4y = -8

4x = 4

4 4

x = 1

2x + y = 3

2(1) + y = 3

2 + y = 3

- 2 - 2

y = 1

(x, y) = (1, 1)

**Answer:**

The solution of an equation with two variables (x and y) is an ordered pair (x, y).

**Step-by-step explanation:**

**Answer:**

Greatest common factor of and is

**Step-by-step explanation:**

**Greatest common factor is the common factor for two or more numbers such that greatest common factor divides both the number. **

**We find Greatest common factor by**

**doing prime factorization and then**

**taking common factors from all the factors and**

**if they do not have nay term common then Greatest common factor is 1.**

Given Numbers are and

First we do prime factorization of .

15 can be written as product of prime 3 and 5, so

and Similarly, can be written as,

Thus, taking common from both the terms,we get,

**Greatest common factor as **

Multiply the GCF of the numerical part 3 and the GCF of the variable part x^2y to get

3x^2y.

3x^2y.